The influence of oxygen saturation on the relationship between hemoglobin mass and VO2max - Goodrich, J. A.; Ryan, B. J.; Byrnes, W. C. (Sports Medicine International Open, 2018)
Hemoglobin mass (tHb) is a key determinant of maximal oxygen uptake (VO2max). We examined whether oxyhemoglobin desaturation (SaO2) at VO2max modifies the relationship between tHb and VO2max at moderate altitude (1,625 m). Seventeen female and 16 male competitive, endurance-trained moderate-altitude residents performed two tHb assessments and two graded exercise tests on a cycle ergometer to determine VO2max and DeltaSaO2. In males and females respectively, VO2max (ml·kg-1·min-1) ranged from 62.5-83.0 and 44.5-67.3; tHb (g·kg-1) ranged from 12.1-17.5 and 9.1-13.0; and SaO2 at VO2max (%) ranged from 81.7-94.0 and 85.7-95.0. tHb was related to VO2max when expressed in absolute terms and after correcting for body mass (r=0.94 and 0.86, respectively); correcting by DeltaSaO2 did not improve these relationships (r=0.93 and 0.83). Additionally, there was a negative relationship between tHb and SaO2 at VO2max (r=-0.57). In conclusion, across a range of endurance athletes at moderate altitude, the relationship between tHb and VO2max was found to be similar to that observed at sea level. However, correcting tHb by DeltaSaO2 did not explain additional variability in VO2max despite significant variability in ?SaO2; this raises the possibility that tHb and exercise-induced DeltaSaO2 are not independent in endurance athletes.